PREDICTION OF FINANCIAL REPORTING FRAUD WITH CROWE’S FRAUD PENTAGON MODEL - Harti Budi Yanti; Sekar Mayangsari; Slamet Wiyono; Ice Nasyrah Noor; Melinda Siregar; Intan Desiani (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study aims to examine the factors that influence fraudulent financial statements using the Crowe's Pentagon model approach. There are five dimensions in this model including Pressure, Opportunity, Rationalization, competence and arrogance. Financial instability, and leverage, is a proxy for measuring the Pressure variable. Composition of Directors and Head of Internal Auditor turnover is a proxy for measuring the Opportunity variable. Restatement times of financial statements and Change in accounting policy, become a proxy for measuring the Rationalization variable. Undeclared Policies and Special purpose entities are proxies for measuring Competence variables. CEO arrogance is measured by the frequency of CEO photo views. The research sample is 115 firm year companies listed on the LQ 45 index with an observation period of 2017 to 2019. The results of the study prove that the head of internal audit turnover, Restatement times, Change in Accounting policy, Special purpose entities and also CEO Picture have a positive effect on financial fraud. statement.